Exosomes as Emerging Drug Delivery and Diagnostic Modality for Breast Cancer: Recent Advances in Isolation and Application - Kumar D.N.; Chaudhuri A.; Aqil F.; Dehari D.; Munagala R.; Singh S.; Gupta R.C.; Agrawal A.K. (My University, 2025)
Breast cancer (BC) is the most common type of malignancy which covers almost one-fourth of all the cancers diagnosed in women. Conventionally, chemo-, hormonal-, immune-, sur-gery, and radiotherapy are the clinically available therapies for BC. However, toxicity and other related adverse effects are still the major challenges. A variety of nano platforms have been reported to overcome these limitations, among them, exosomes provide a versatile platform not only for the diagnosis but also as a delivery vehicle for drugs. Exosomes are biological nanovesicles made up of a lipidic bilayer and known for cell-to-cell communication. Exosomes have been reported to be present in almost all bodily fluids, viz., blood, milk, urine, saliva, pancreatic juice, bile, peritoneal, and cerebrospinal fluid. Such characteristics of exosomes have attracted immense interest in cancer diagnosis and therapy. They can deliver bioactive moieties such as protein, lipids, hydrophilic as well as hydrophobic drugs, various RNAs to both distant and nearby recipient cells as well as have specific biological markers. By considering the growing interest of the scientific community in this field, we comprehensively compiled the information about the biogenesis of exosomes, various isolation methods, the drug loading techniques, and their diverse applications in breast cancer diagnosis and therapy along with ongoing clinical trials which will assist future scientific endeavors in a more organized direction. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.